Determinants of internet financial reporting by Saudi listed companies - Mohammed Saleh Awadh Bajaher (2006)
This study explores the status of Internet Financial Reporting among Saudi listed companies. As at 30th September 2006, there were 84 companies listed in Saudi Stock Market. The results reveal that 67 (80%) of these companies have Web site. Of these 67 companies, only 38 (57%) provided some forms of financial information on their Website. The findings indicate that the status of Internet Financial Reporting among Saudi's listed companies is still behind those of developed countries and even some developing countries like Malaysia. This study then examines factors that influence the extent of Internet Financial Reporting. Three dominant factors identified by previous studies, i.e. company size, leverage and profitability were tested for this purpose. The results of multiple regression analysis reveal that only company size contributed significantly to the extent of financial information disclosed on the Internet among Saudi companies. Leverage and profitability are not significantly associated with the extent of Internet Financial Reporting. The findings of this study shed some lights of the status of Internet Financial Reporting among Saudi companies. More importantly, it opens up possibilities for further study of Internet Financial Reporting among Gulf countries.